2002
DOI: 10.1053/bbmt.2002.v8.pm12234171
|View full text |Cite
|
Sign up to set email alerts
|

Correction of phenotype in a thalassemia mouse model using a nonmyeloablative marrow transplantation regimen

Abstract: Gene therapy, the replacement of normal human beta- or gamma-globin genes into the hematopoietic stem cells of patients with homozygous beta-thalassemia, is a promising therapy for the future. High-level lineage-specific stable globin expression in transduced cells reinfused into patients in an autologous transplantation setting could be curative, if successful. Previous studies have shown high-level donor chimerism in nonmyeloablated non-thalassemic hosts. We have now studied the conditions for stable long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…In conclusion, a key success factor in our safe and efficacious program is the sequential use of immunosuppressive pharmacotherapy followed by a reduced-toxicity conditioning program rather than striving for maximum intensity of the conditioning program itself, paired with a relatively high number of hematopoietic progenitor cells (on average >5 × 10 6 CD34 + cells/ kg of recipient weight [5,20]), which resulted in a low incidence of toxicity and durable engraftment in this group of patients with high-risk class 3 thalassemia.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, a key success factor in our safe and efficacious program is the sequential use of immunosuppressive pharmacotherapy followed by a reduced-toxicity conditioning program rather than striving for maximum intensity of the conditioning program itself, paired with a relatively high number of hematopoietic progenitor cells (on average >5 × 10 6 CD34 + cells/ kg of recipient weight [5,20]), which resulted in a low incidence of toxicity and durable engraftment in this group of patients with high-risk class 3 thalassemia.…”
Section: Discussionmentioning
confidence: 99%
“…Donor chimerism was calculated as CD45.1/(CD45.1 þ CD45.2) as nucleated red blood cells do not label with CD45.1 or CD45. 2 For lineage analysis, we labeled bone marrow with rat-antimouse Ly6G/GR-1 (8C5 hybridoma), CD45R/B-220 (RA3 hybridoma) or CD3 (T cells) (PharMingen) mAbs. Donor specificity was detected using a mouse-anti-mouse biotin-CD 45.1 mAb (PharMingen).…”
Section: Flow Cytometry Engraftment and Lineage Analysismentioning
confidence: 99%
“…In previous studies we, as well as others, have shown high levels of engraftment into nontreated hosts and into minimally treated hosts. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] The key to high levels of engraftment in these models has generally been infusion of high numbers of donor cells to compete with resident or residual host marrow cells. Data from these studies have suggested that marrow space might not need to be 'opened' by cytotoxic host treatment for stem cell engraftment to occur.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Several investigators have shown the potential of non-myeloablative or reduced intensity (RI) conditioning followed by AlloSCT to reduce regimen-related morbidity, regimen-related mortality (RRM) and potentially future late effects in patients with both malignant and nonmalignant disorders. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] A recent review by our group has summarized the results to date following RI conditioning for allogeneic stem cell transplantation (RI-AlloSCT). 35 Recently, successful engraftment has been demonstrated after reduced intensity UCBT (RI-UCBT) in adult recipients.…”
Section: Introductionmentioning
confidence: 99%